Green Innovation, Firm Size, and Environmental Performance: The Moderating Role of Corporate Governance in Indonesian Food and Beverage Firms - Putu Vina Marcyella Griadhi; Lucy Sri Musmini; I Made Pradana Adiputra (Jurnal Ilmiah Akuntansi, 2026)
This study examines whether green innovation and firm size are associated with the environmental performance of Indonesian food and beverage firms and whether corporate governance moderates these relationships. The sample comprises 24 food and beverage firms listed on the Indonesia Stock Exchange from 2019 to 2023, resulting in 120 firm-year observations. Data were obtained from annual and sustainability reports and analyzed using panel-data regression and moderated regression analysis in Stata, with return on assets included as a control variable. The results show that neither green innovation nor firm size is significantly associated with environmental performance, either individually or jointly. Return on assets also has no significant relationship with environmental performance. Furthermore, corporate governance does not significantly moderate the relationship between green innovation and environmental performance or that between firm size and environmental performance. These findings indicate that adopting green initiatives and possessing greater organizational resources do not necessarily result in stronger environmental performance. The study also suggests that corporate governance mechanisms may be insufficient to translate green innovation and firm-level resources into environmental outcomes without stronger implementation, monitoring, and regulatory support.